1996
DOI: 10.1099/13500872-142-5-1087
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transfer of amylovoran and stewartan synthesis between Erwinia amylovora and Erwinia stewartii

Abstract: DNA fragments with ams genes of Erwinia amylovora and cps genes of Erwinia stewartii were transferred to exopolysaccharide (EPS)-deficient mutants of the other species. The resulting EPSs were characterized by sensitivity to EPS-dependent bacteriophages, staining with amylovoran-specific fluorescein-isothiocyanate-labelled lectin and chemical techniques, such as determination of the sugar composition and methylation analysis in order to distinguish between amylovoran and stewartan. Degradation by the stewartan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…However, we showed that virulence of either pathogen is not influenced by the nature of the EPS produced when the host plants are infected by manual inoculation (Table 1). This is consistent with the finding by Bernhard et al . (1996) showing that the P. stewartii strain producing a hybrid stewartan was virulent when assayed by manual inoculation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, we showed that virulence of either pathogen is not influenced by the nature of the EPS produced when the host plants are infected by manual inoculation (Table 1). This is consistent with the finding by Bernhard et al . (1996) showing that the P. stewartii strain producing a hybrid stewartan was virulent when assayed by manual inoculation.…”
Section: Discussionsupporting
confidence: 94%
“…Bernhard et al . (1996) showed that expression of the ams‐I gene cluster in P. stewartii led to the production of partially pyruvylated stewartan.…”
Section: Resultsmentioning
confidence: 99%
“…Ew. amylovora mainly produces the acidic heteropolymer amylovoran, composed of repeating pentamer units, each with four galactose residues and one glucuronic acid residue Mol Gen Genet (1997) 256: 72±83 (Smith et al 1990;Bernhard et al 1996). The complete ams gene cluster responsible for the biosynthesis of amylovoran has been cloned and sequenced (Bernhard et al 1993;Bugert and Geider 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Transfer of the ams cluster into Ew. stewartii mutants de®cient in capsule synthesis results in the production of amylovoran, as shown by sugar analysis and the use of EPS-speci®c phage depolymerases (Bernhard et al 1996). The ams gene cluster of Ew.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to some differences in the acetylation pattern and substitution by succinyl groups, this glucose residue is a major difference for EPS of E. pyrifoliae and amylovoran of E. amylovora. Amylovoran produced in E. stewartii cps mutants carrying pEA109 is not acetylated, in contrast to stewartan synthesized in E. amylovora ams mutants with pES2144, a cosmid with the cps genes of Pantoea (Erwinia) stewartii (Bernhard et al, 1996). Genes for acetylation should reside apart from the ams region inserted in plasmid pEA109.…”
mentioning
confidence: 99%